Genetic and molecular interactions between H∆CT, a novel allele of the notch antagonist hairless, and the histone chaperone Asf1 in Drosophila melanogaster - Maier, Dieter; Bauer, Milena; Boger, Mike; Sanchez Jimenez, Anna; Fechner, Johannes; Scharpf, Janika; Preiß, Anette; Nagel, Anja Christina (Genes, 2023)
Cellular differentiation relies on the highly conserved Notch signaling pathway. Notch activity induces gene expression changes that are highly sensitive to chromatin landscape. We address Notch gene regulation using Drosophila as a model, focusing on the genetic and molecular interactions between the Notch antagonist Hairless and the histone chaperone Asf1. Earlier work implied that Asf1 promotes the silencing of Notch target genes via Hairless (H). Here, we generate a novel HΔCT allele by genome engineering. Phenotypically, HΔCT behaves as a Hairless gain of function allele in several developmental contexts, indicating that the conserved CT domain of H has an attenuator role under native biological contexts. Using several independent methods to assay protein-protein interactions, we define the sequences of the CT domain that are involved in Hairless-Asf1 binding. Based on previous models, where Asf1 promotes Notch repression via Hairless, a loss of Asf1 binding should reduce Hairless repressive activity. However, tissue-specific Asf1 overexpression phenotypes are increased, not rescued, in the HΔCT background. Counterintuitively, Hairless protein binding mitigates the repressive activity of Asf1 in the context of eye development. These findings highlight the complex connections of Notch repressors and chromatin modulators during Notch target-gene regulation and open the avenue for further investigations.
Die Zeichen "∆CT" sind im Titel hochgestellt
Gesehen am 16.10.2024